A spontaneous electric field membrane bioreactor with the innovative Cu‐nanowires conductive microfiltration membrane for membrane fouling mitigation and pollutant removal. (21st April 2019) - Yin, Xiafei; Li, Xiufen; Wang, Xinhua; Ren, Yueping; Hua, Zhaozhe
Abstract : Abstract: In this study, a spontaneous electric field membrane bioreactor (SEF‐MBR), equipped with the innovative Cu‐nanowires conductive microfiltration membrane, was developed to achieve membrane fouling mitigation and high‐quality effluent. The membrane fouling was significantly mitigated due to the presence of spontaneous electric field that the intensity of the spontaneous electric field in the established SEF‐MBR was up to 0.073 V/cm. After over 2‐month operation, the membrane flux of SEF‐MBR was 2.1 times that of the control reactor. The thickness of fouling layer on the Cu‐nanowires conductive membrane surface was about 80 μm, which was far thinner than that on the surface of commercial polyvinylidene fluoride (PVDF) membrane. Meanwhile, it was featured with the lower microbe density and extracellular polymeric substance (EPS) content. The effluent quality of SEF‐MBR met the first‐class discharge standards, and the removal rates were 94.5% for chemical oxygen demand (COD), 99.8% for NH 4 + - N, 78.5% for total nitrogen (TN), and 86.6% for total phosphorus (TP). The established system with the innovative Cu‐nanowires conductive membrane showed a promising prospect for using the spontaneous electric field to mitigate membrane fouling and achieve high‐quality effluent without extra power consumption. Practitioner points: The innovative Cu‐NWs conductive microfiltration membrane was prepared. The spontaneous electric field in the novel SEF‐MBR mitigated membrane fouling. The fouling layer of the novel SEF‐MBR was thinner with lower microbe and EPS content. The effluent quality of the novel SEF‐MBR met the first‐class discharge standard. Abstract : The Cu‐nanowires conductive microfiltration membrane with low resistance was prepared as the cathode. Due to the presence of the electric field force, the contaminants were prone to deviate from the membrane surface, thus mitigating membrane fouling.